Kepribadian Proaktif sebagai Mediator antara Dukungan Orangtua dan Efikasi Diri dalam Pengambilan Keputusan Karier Siswa Sekolah Menengah Pertama - Karina, Nungky Karina; Salim, Rose Mini Agoes (Jurnal Kajian Bimbingan dan Konseling, 2020)
This study aims to examine the role of proactive personality as a mediator of the relationship between parental support in career and self-efficacy in career decision making in junior high school students. The research sample of 140 people obtained by accidental sampling. The instruments used were Career-Related Parent Support Scale, Career Decision Self-Efficacy Short Form, and Proactive Personality Scale which had been adapted into Indonesian. The data were analyzed by regression using PROCESS macros suggested by Hayes. The results showed that proactive personality partially mediates the relationship between parental support in career and self-efficacy in career decision making. Further analysis shows that: (1) proactive personality partially mediates the relationship between parental support in the form of instrumental assistance and self-efficacy in career decision making; (2) proactive personality partially mediates the relationship between parental support in the form of career modeling and self-efficacy in career decision making; (3) proactive personality partially mediates the relationship between parental support in the form of emotional support with self-efficacy in career decision making; and; (4) proactive personality fully mediates the relationship between parental support in the form of verbal encouragement with self-efficacy in career decision making. The implications, limitations and suggestions for further research are discussed as follows.